Synthesis and characterization of poly(ethylene glycol)-poly(D,L-lactide-co-glycolide) poly(ethylene glycol) tri-block co-polymers modified with collagen: a model surface suitable for cell interaction - ERCAN, FERİHA; ŞİRVANCI, SERAP (TAYLOR & FRANCIS LTD, 2006)
This study focused oil the synthesis and characterization of poly(ethylene glycol)-poly(D,L-lactide-co-glycolide)-poly(ethylene glycol) tri-block co-polymer (PEG-PDI-LG-PEG), and its modification with type-I collagen. To this aim, a PEG-PDLLG-PEG tri-block co-polymer was synthesized in two steps by reacting poly(ethylene glycol)bis(carboxymethyl)ether with thionyl chloride to obtain all acyl-halide-terminated poly(ethylene glycol) and Subsequently Coupling this compound to hydroxyl-terminated poly(D,L-lactide-co-glycolide) (PDLLG). The new carboxyl end-groups of PEG-PDLLG-PEG were subsequently reacted with N-hydroxysuccinimide (NHS) in the presence of the hetero-bifunctional cross-linking agent dicyclohexylcarbodiimide (DCC) in order to activate the co-polymer for coupling with collagen. PEG-PDLLG-PEG and its activated form PEG-PDLLG-NHS were characterized by Fourier transform infrared (FT-IR) and H-1-NMR spectroscopy. Molecular weights of the polymeric products were determined by SEC. Type-I collagen in phosphate buffer was reacted with PEG-PDLLG-NHS. The resultant product. PEG-PDLLG-Col, was characterized by FT-IR. This biopolymer was used for preparation of a suitable Surface for cell growth experiment. To measure the degree of cell proliferation, the films prepared with PDLLG. PEG-PDLLG-NHS and PEG-PDLLG-Col were seeded with L929 mouse fibroblasts. Cell growth was followed by SEM photography and quantitated by the neutral red uptake assay. It was shown that the attachment of collagen significantly increased the number of cells oil the co-polymers.
Keywords: poly(D,L-lactide-co-glycolide); poly(ethylene glycol); collagen; cell viability; fibroblast; cell culture; biomaterial; ACRYLIC-ACID; ADHESION